2018
DOI: 10.21608/mjcu.2018.59877
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Level Changes in Type 2 Diabetes

Abstract: Background: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion or insulin action, or both. Diabetes and its complications have become a major public health problem in the world and its prevention has become a public health priority. Hepcidin, a 25-amino-acid antimicrobial peptide, is the central regulator of iron homeostasis. Under normal circumstances, hepcidin expression and subsequent release into plasma prevents further absorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Although previous evidence has shown that iron overload increases the risk of T2DM and cognitive impairment ( 16 , 42 ), our meta-analysis revealed that T2DM patients have more iron deposition in the DGM. This may be due to the reciprocal effects of T2DM and iron overload/accumulation ( 13 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous evidence has shown that iron overload increases the risk of T2DM and cognitive impairment ( 16 , 42 ), our meta-analysis revealed that T2DM patients have more iron deposition in the DGM. This may be due to the reciprocal effects of T2DM and iron overload/accumulation ( 13 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%